Evaluation of Memorial Sloan‐Kettering Cancer Center and International Extranodal Lymphoma Study Group prognostic scoring systems to predict Overall Survival in intracranial Primary CNS lymphoma. Issue 3 (5th February 2018) - Jahr, Guro; Broi, Michele Da; Holte, Harald; Beiske, Klaus; Meling, Torstein R.
Abstract: Objectives: To evaluate the validity of Memorial Sloan‐Kettering Cancer Center (MSKCC) and International Extranodal Lymphoma Study Group (IELSG) prognostic scoring systems for Overall Survival (OS) in intracranial Primary CNS lymphoma (PCNSL) of all patients diagnosed at a single center. Material and Methods: Pretreatment clinical factors including tumor characteristics and histology, treatment, and survival of PCNSL patients with diagnostic biopsies over a 12‐year period (2003–2014) were retrieved from a prospective database at Oslo University Hospital. Results: Seventy‐nine patients with intracranial PCNSL were identified. The female:male ratio was 1:1.63 and the median age was 65.3 years [range 18.9–80.7]. Involvement of deep brain structures was shown in 63 patients. Six patients were MSKCC risk group 1, 35 patients were in risk group 2, and 38 patients were in risk group 3. International Extranodal Lymphoma Study Group scores were <2 in 17 patients (22%). After a median follow‐up of 70.5 months, 55 patients were dead. Median OS was 16.4 months [range 0.2–157.7]. Age, sLDH by recursive partitioning analysis (RPA), Eastern Cooperative Oncology Group score (ECOG), lesion size, involvement of deep brain structures, IELSG score, and MSKCC score were significant factors for OS in univariate analysis. Multivariate analysis confirmed the significance of age ( p  < .05), sLDH by RPA ( p  < .005), ECOG ( p  < .05), and deep brain structure involvement ( p  < .05) for OS. The six‐tiered IELSG scores had to be dichotomized according to RPA analysis into <2 and ≥2 in order to have prognostic value. In contrast, when using the three‐tiered MSKCC, three distinct risk groups were identified. Conclusions: Our study failed to verify the IELSG, but validated the use of MSKCC for prognostication of OS in intracranial PCNSL. Abstract : Despite the uncertainty in survival prediction, existing prognostic tools can facilitate clinical decision making. Even though several prognostic scoring systems have been proposed, stratification of Primary CNS lymphoma (PCNSL) patients is still challenging for clinicians. Our study failed to verify the IELSG, but validated the use of MSKCC for prognostication of OS in intracranial PCNSL.